CD4+ and Perivascular Foxp3+ T Cells in Glioma Correlate with Angiogenesis and Tumor Progression - Mu, Luyan; Yang, Changlin; Gao, Qiang; Long, Yu; Ge, Haitao; DeLeon, Gabriel; Jin, Linchun; Chang, Yifan (Emily); Sayour, Elias J.; Ji, Jingjing; Jiang, Jie; Kubilis, Paul S.; et al. (Frontiers in Immunology, 2017)
Background： Angiogenesis and immune-cell infiltration are key features of gliomas and their manipulation of the microenvironment, but their prognostic significance remains indeterminate. We evaluate the interconnection between TIL and tumor blood-vasculatures in the context of glioma progression. Methods： Paired tumor tissues of 44 patients from 3-tumor recurrent groups: diffuse astrocytomas (DA) recurred as DA, DA recurred as GBM, and GBM that recur as GBM were evaluated by genetic analysis, immunohistochemistry for tumor-blood vessel density, TIL subsets, and clinical outcomes. These cells were geographically divided into perivascular and intratumoral TILs. Associations were examined between these TILs, CD34+ tumor blood-vessels, and clinical outcomes. To determine key changes in TIL subsets, microarray data of 15-paired tumors from patients who failed anti-angiogenic therapy- bevacizumab, and 16-paired tumors from chemo-naïve recurrent GBM were also evaluated and compared. Results：Upon recurrence in primary gliomas, similar kinetic changes were found between tumor blood-vessels and each TIL subset in all groups, but only CD4+ including Foxp3+ TILs, positively correlated with the density of tumor blood-vessels. CD4 was the predominant T cell population based on gene-transcripts in primary GBMs, and increased activated CD4+ T cells were revealed in Bevacizumab resistant recurrent tumors (not in chemo-naïve recurrent tumors). Among these TILs, 2/3 of them were found in the perivascular niche; Foxp3+ T cells in these niches not only correlated with the tumor-vessels, but were also an independent predictor of shortened recurrence-free 22 survival (RFS) (HR= 4.199, 95% CI 1.522–11.584, p=0.006). Conclusions： The minimal intratumoral T cell infiltration and low detection of CD8 transcripts in primary GBMs can potentially limit antitumor response. CD4+ and perivascular Foxp3+ TILs associate with tumor angiogenesis and tumor progression of glioma patients. Our results suggest that combining anti-angiogenic agents with immunotherapeutic approaches may help improve the antitumor efficacy for patients with malignant gliomas.